Human Cerebrospinal Fluid Modulates Pathways Promoting Glioblastoma Malignancy - Carrano, Anna; Zarco, Natanael; Phillipps, Jordan; Lara-Velazquez, Montserrat; Suarez-Meade, Paola; Norton, Emily S.; Chaichana, Kaisorn L.; Quiñones-Hinojosa, Alfredo; Asmann, Yan W.; Guerrero-Cázares, Hugo (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is the most common and devastating primary cancer of the central nervous system in adults. High grade gliomas are able to modify and respond to the brain microenvironment. When GBM tumors infiltrate the Subventricular zone (SVZ) they have a more aggressive clinical presentation than SVZ-distal tumors. We suggest that cerebrospinal fluid (CSF) contact contributes to enhance GBM malignant characteristics in these tumors. We evaluated the impact of human CSF on GBM, performing a transcriptome analysis on human primary GBM cells exposed to CSF to measure changes in gene expression profile and their clinical relevance on disease outcome. In addition we evaluated the proliferation and migration changes of CSF-exposed GBM cells in vitro and in vivo. CSF induced transcriptomic changes in pathways promoting cell malignancy, such as apoptosis, survival, cell motility, angiogenesis, inflammation, and glucose metabolism. A genetic signature extracted from the identified transcriptional changes in response to CSF proved to be predictive of GBM patient survival using the TCGA database. Furthermore, CSF induced an increased in viability, proliferation rate, and self-renewing capacity, as well as the migratory capabilities of GBM cells in vitro. In vivo, GBM cells co-injected with human CSF generated larger and more proliferative tumors compared to controls. Taken together, these results provide direct evidence that CSF is a key player in determining tumor growth and invasion through the activation of complex gene expression patterns characteristic of a malignant phenotype. These findings have diagnostic and therapeutic implications for GBM patients. The changes induced by CSF contact might play a role in the increased malignancy of SVZ-proximal GBM.